PENGARUH KOMUNIKASI INFORMASI DAN EDUKASI BERBASIS AUDIOVISUAL TERHADAP PENGETAHUAN, SIKAP DAN MOTIVASI ORANG TUA DALAM PERAWATAN ANAK THALASEMIA DI KABUPATEN KUNINGAN TAHUN 2018 - Sri Fatmawati; Nanang Saprudin; Neneng Aria (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2020)
Background: Problems thalasemia become a bandwagon around the world including in indonesia. Recorded thalasemia patients in indonesia in 2017 namely 15.000 people. The problems often experienced in the case thalasemia is the lack of the older people in giving care for the thalasemia. Preliminary studies known 3 mother has knowledge, attitudes and motivation lacking in child care thalasemia. This report aims to review the influence of education and information communication audiovisual based on knowledge, attitudes and motivation parents in the care of thalasemia at RSUD 45 Kuningan. Research Methods: The kind of research this is experimental, with quasy eksperiment design and design one research group pre-test and post-test design, with a population of 119 people. The sample collection technique using a technique acidental the sampling method of 30 or the number of respondents, by the time research for 1 week. The research instruments used in using a questionnaire. Statistical analysis done in univariat and bivariat with the methods chisquare comparative mcnemar by test. Research Result: The analysis shows increased univariat knowledge about 12 respondents ( 40 % ) having given intervention, 10 respondents ( 33,3 %) suitor positive after given intervention and 11 respondents ( 36,6 % ) have a good motivation in the care of thalasemia having given intervention. The analysis chi-square by test comparative mcnemar obtained the influence of education and information communication audiovisual based on knowledge parents ( p value = 0,002 ), the parents ( p value = 0,002 ), and motivation parents ( p value = 0,001 ) with child care thalasemia post transfusion. Conclusion: The results of the study concluded that is the communication information and education audiovisual based on knowledge , attitudes and motivation parents in the care of thalasemia .Expected parents , and nurses can work together in care for the thalsemia